Analysis technique of translation and measurement shift (shifts) in text of AXA Life contract Indonesia - Pantas Simanjuntak (Politeknik Negeri Bali, 2017)
The research was carried out to analyse a legislative text as a product of translation. It is referred to Seiddel's qualitative data analysis where the data processing was performed by selecting, identification, and tabulating. (2%), compensation (1%), description (2%) discursive creation (5%) generalization (5%), literal translation (10%), modulation (8%), particularization (5%) reduction (5%) completion (4%), and dilation (14%). Meanwhile, the four categories shift are implemented as the following frequency: Intra-system shifts; 90 (52.02%), followed by Unit Shifts 46 (26.59%), Structural Shifts 24 (13.88%), and then Class Shifts 13 (7.51%). The other finding was inaccurateness. It was found that there were inaccurate translation for 5 phrases, and resulted not equivalence ones in rendering the source language into the target language.